The Influence of Digital Learning Facilities and Teachers' Digital Competence on Teacher Performance at SMK Negeri 5 Medan - Elfrida Simanungkalit; Dwi Fany Fransiska Dewi Butar butar; Raymond Fransiskus (Lembaga Pengembangan Kinerja Dosen, 2026)
This study seeks to analyze the influence of digital learning facilities and teachers’ digital competence on the performance of teachers at SMK Negeri 5 Medan. As the education sector undergoes rapid digital transformation, the ability of schools to provide sufficient digital facilities and the capacity of teachers to master digital skills have become critical factors in determining overall performance. The research applied a quantitative approach with a survey technique, involving 40 respondents drawn from the total population of 60 teachers through saturated sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 22. The results of the analysis reveal that both digital learning facilities and teachers’ digital competence significantly and positively affect teacher performance, both individually and collectively. Furthermore, the Adjusted R Square value of 0.981 indicates that 98.1% of the variation in teacher performance can be explained by these two independent variables, while only 1.9% is influenced by other factors outside the model. These findings underscore the importance of ensuring the availability and accessibility of adequate digital learning facilities as well as strengthening teachers’ digital competence through continuous training and professional development. By prioritizing these aspects, schools can optimize teacher performance and effectively respond to the challenges of the digital era.